Pottery traditions of the Andronovo (Fedorovo) population of the steppe Altai (based on materials from the settlement of Zharkovo-3) - Papin D.V. (Вестник археологии, антропологии и этнографии, 2021)
Zharkovo 3 settlement is located in the south of Western Siberia in the steppe Altai. The site was studied by archaeologists of the Altai State University and they discovered two building horizons: one of the Andronovo time (one house was studied) and the other of the Late Bronze Age (two structures and a soot pit). The paper presents the results of a comprehensive analysis of the Andronovo (Fedorovo) ceramics of the Zharkovo 3 settlement. Fragments of 74 different vessels were used to analyze the ornamentation. The method of V.F. Gening was used. The authors conducted the analysis of shapes and ornamentation of the ancient tableware, and analysis of the technology of its manufacture. It has been established that the collection contains vessels of cap- and pot-shaped forms, the predominant technique of ornamentation of which is stamping. The ornamental compositions mainly consist of four or more different motifs. A series of 49 samples, apparently from 47 vessels, was subjected to technical and technological analysis. The method of study of ceramics, developed by A.A. Bobrinsky and followers of his school within the framework of the historical and cultural approach, was used. The potters of the village preferred medium-plastic clay of medium iron content as the raw material. The main recipe for the paste composition was ‘clay + chamotte + organics’. Research into the construction of the pottery has revealed consistent skills in its manufacture. The patchwork-lumpy and spiral-patchwork methods of forming the vessel hollow body, recorded in the settlement, are characteristic of the Andronovo ceramics throughout its distribution area. It can be stated that the Andronovo population, who left the pottery of the Zharkovo 3 settlement, achieved a certain unity of cultural traditions in selection of the raw materials and paste composition. Almost all vessels of the site exhibited the use of the same type of mineral additives — chamotte. Deviations in concentration and dimension of its particles are associated with individual differences in the skills of the potters of the settlement. The presence on the site of individual vessels with pronounced differences in manufacturing technology should be regarded as examples of imports.